الآليات الإقناعية في شعر الكميت بن زيد الأسدي - السبتي, سلطاني (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الورقة البحثية إلى دراسة الآليات الحجاجية التي وظفها الكميت بن زيد الأسدي من أجل الدفاع عن حق أصحابه بني هاشم في الخلافة، عبر رصد أهم الآليات الحجاجية وتصنيفها، والكشف عن مدى تأثيرها في المتلقي سواء ذلك المقصود بالخطاب أي خصوم بني هاشم أو المتلقي حيثما كان. ولتحقيق هذا الهدف عمدنا إلى ضبط الجهاز المصطلحي ثم حددنا طبيعة الآليات الحجاجية عموما لنقوم برصد وتتبع هذه الآليات الحجاجية من خلال ديوان الكميت. This research paper aims to identify the Hajj mechanisms employed by Al-Kamit bin Zaid al-Asadi in order to defend the right of his companions Bani Hashem to the caliphate. That is so by monitoring and classifying the most important Hajj mechanisms and revealing the extent of their impact on the recipient, whether that means the speech, i.e. opponents of Bani Hashem or the recipient wherever he is. To achieve this goal, we have adjusted the terminological apparatus and then determined the nature of the Hajj mechanisms in general to monitor and track these pilgrimage mechanisms through the Diwan of Al-Kumit.
مقال
Keywords: الآليات – الإقناع – الخطاب – الشعري - الكميت; mechanisms-speech - persuasion - poetry- Al-Kumit